LINKED AND MATCH BETWEEN THE MICE STUDY PROGRAM OF THE JAKARTA STATE POLYTECHNIC AND PT ANGAN KREASI SEMESTA: A CASE STUDY OF MARKETING ACTIVITIES OF THE 2024 INDONESIAN HALAL EXPORT EXHIBITION - Rimsky K Judisseno; Angelysia Kusuma Dewi Rizky; Etty Khongrat; Djuni Akbar (ZILLZELL MEDIA PRIMA, 2025)
This study explores the alignment between academic instruction in the MICE (Meeting, Incentive, Convention, and Exhibition) Study Program at the Jakarta State Polytechnic and the practical demands of the event management industry, based on fieldwork conducted at PT Angan Kreasi Semesta during the Halal Export Indonesia 2024 event. Using qualitative descriptive methods, data were collected through participatory observation, daily logbook entries, and document analysis. The findings reveal a partial yet significant alignment between theoretical coursework—particularly in marketing, sponsorship, and public relations—and the tasks performed during the internship. Approximately 75–85.7% of the academic content was found to be applicable in practice, as evidenced by activities such as sponsorship proposal development, promotional content creation, and media partnership management. However, notable competency gaps emerged in digital advertising strategies, social media content planning, and legal procedures related to partnership agreements. The study also highlights the development of key SCANS-based competencies, including communication, resource management, and technological literacy. These results underscore the need to enhance the curriculum by integrating practical modules on digital marketing analytics, legal documentation, and PR tools, as well as strengthening institutional partnerships with industry players. The study contributes to the discourse on curriculum-industry alignment and offers pedagogical recommendations to improve graduate employability in the event management sector.